2023
DOI: 10.1002/smll.202207798
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Regulation Effects of ssDNA on the Mimetic Oxidase and Peroxidase Activities of Covalent Organic Frameworks

Abstract: Nanomaterials with enzyme mimetic activity have attracted extensive attention, especially in the regulation of their catalytic activities by biomolecules or other polymers. Here, a covalent organic framework (Tph‐BT COF) with excellent photocatalytic activity is constructed by Schiff base reaction, and its mimetic oxidase activity and peroxidase activity is inversely regulated via single‐stranded DNA (ssDNA). Under light‐emitting diode (LED) light irradiation, Tph‐BT exhibited outstanding oxidase activity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…As the main form of uranium, UO 2 2+ is distributed in the Earth’s crust and oceans. , Due to the continuous escalation of human activities, such as nuclear testing, nuclear accidents, and the discharge of wastewater from nuclear power plants, uranium’s profound chemical and radiological toxicity poses an increased risk to human health. , Therefore, it is necessary to develop a sensing platform with high sensitivity and accuracy to realize UO 2 2+ detection (Figure a). Accordingly, based on the unique structure and electronic properties of actinide U, the hybridization of 5d-6f orbital results in the linear structure of UO 2 2+ (OUO) 2+ . ,, The presence of the single electron on the N of the imine (–NH) in the oxTMB can form the complex with UO 2 2+ ions. , In detail, the binding energy peak of U 4f of the complex is observed in the XPS spectrum (Figure b). Moreover, the N 1s spectra of oxTMB with and without UO 2 2+ were compared, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main form of uranium, UO 2 2+ is distributed in the Earth’s crust and oceans. , Due to the continuous escalation of human activities, such as nuclear testing, nuclear accidents, and the discharge of wastewater from nuclear power plants, uranium’s profound chemical and radiological toxicity poses an increased risk to human health. , Therefore, it is necessary to develop a sensing platform with high sensitivity and accuracy to realize UO 2 2+ detection (Figure a). Accordingly, based on the unique structure and electronic properties of actinide U, the hybridization of 5d-6f orbital results in the linear structure of UO 2 2+ (OUO) 2+ . ,, The presence of the single electron on the N of the imine (–NH) in the oxTMB can form the complex with UO 2 2+ ions. , In detail, the binding energy peak of U 4f of the complex is observed in the XPS spectrum (Figure b). Moreover, the N 1s spectra of oxTMB with and without UO 2 2+ were compared, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…23,40,41 The presence of the single electron on the N of the imine (−N�H) in the oxTMB can form the complex with UO 2 2+ ions. 42,43 In detail, the binding energy peak of U 4f of the complex is observed in the XPS spectrum (Figure 4b). Moreover, the N 1s spectra of oxTMB with and without UO 2 2+ were compared, respectively.…”
Section: ■ Introductionmentioning
confidence: 95%
“…37 These results indicated that the presence of PFOA could selectively bind to its Apt for forming DNA secondary structure-based conformation change, weakening of the π−π interactions to trigger the dissociation of Apt away from the surface of PtCoNPs@g-C 3 N 4 . 44 As a result, the oxidase-like activity of Apt-PtCoNPs@ g-C 3 N 4 was activated and restored to produce O 2…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The surface of COFs has abundant functional groups and active sites, which are po tential targets for constructing nanozymes. Zhang et al [26] used a solvothermal synthesis method to prepare an imine-linked tetragonal COF nanozyme (Tph-BDP) through the combination of [C2 + C4] (Figure 3A). Under the illumination condition of LED light, Tph BT has high simulated oxidase activity.…”
Section: Design Principle Of Cof Nanozymesmentioning
confidence: 99%